The effect of differential learning on the development of inferential thinking: for Fifth Grade female students - Owiz, Furat Alwan; Zayer, Saad Ali (Al-Adab Journal, 2021)
The research aims to know the effectiveness of differential learning in the development of inferential thinking among fifth literary students, because of the impact of any differential learning in making students able to extrapolate, conclude, analyze and interpret when studying Arabic grammar, which reduces the difficulty of the subject, by applying the five steps For learning exclusively, starting from the problem stage, then the reference phase, then mental processes, the semantic network, and finally the semantics.